Surgical Treatment of Sprengel's Deformity: A Systematic Review and Meta-Analysis - Paola Zarantonello; Giovanni Luigi Di Gennaro; Marco Todisco; Piergiorgio Cataldi; Stefano Stallone; Andrea Evangelista; Daniele Ferrari; Diego Antonioli; Giovanni Trisolino (MDPI AG, 2021)
(1) Background: Sprengel's deformity (SD) is a rare congenital anomaly caused by failure in the descent of the scapula. We aimed to systematically review the current literature reporting data from children undergoing surgery for SD, in order to explore the rate of success and complications of the different surgical techniques, possibly providing recommendations about the management of SD in children. (2) Methods: we electronically searched the literature from Ovid, MEDLINE and the Cochrane Library databases. Demographic data, surgical procedures, outcomes and complications were analyzed. We categorized surgical procedures into five groups. (3) Results: 41 articles met the inclusion criteria, showing a poor overall study quality; 674 patients (711 shoulders) were analyzed. Green's and Woodward's procedures, both aiming the scapular relocation in a more anatomical position, were the most commonly used techniques. We counted 168 adverse events (18 major complications). The best clinical and cosmetic results seem to be achieved when surgery is performed in children aged less than eight years. (4) Conclusions: this paper represents the first systematic review reporting qualitative and quantitative data about the surgical treatment of SD. Surgery for SD seems to be effective in increasing the shoulder's range of motion and improving the cosmetic appearance in almost all cases, with a low rate of major complications.